(untitled) (Physical Education, Health and Social Sciences, 2025)
The combination of emergency medical procedures, trauma patients present an elevated threat of pulmonary aspiration so Rapid Sequence Induction (RSI) becomes essential for their airway management. The selection between ketamine and propofol as anesthetic agents directly influences both the stability of blood circulation and the respiratory system. The pharmacokinetic differences between these drugs do not prevent their regular usage in RSI protocols. This objective of this to, comparative study of propofol an ketamine in trauma patients with a focus on hemodynamics and respiratory effect. The data analysis was involved collecting and preprocessing patient data, categorizing them into propofol and ketamine groups, and assessing key hemodynamic (HR, SBP, DBP, MAP) and respiratory (RR, SpO₂, EtCO₂) parameters. Descriptive statistics was summarizing the data using mean ± SD or median ± IQR for continuous variables and percentages for categorical variables. The studied patient population aged from 18 to 65 years. Those given ketamine treatment had a mean patient age of 42.02 years while the propofol-treated patients had a mean age of 38.76 years. The age-related data points between groups were equivalent thus maintaining equal evaluation of the agents across various age brackets. The measured systolic blood pressure values extended between 98–157 mmHg in the ketamine group and 92–160 mmHg in the propofol group yet the propofol group demonstrated wider pressure variation. The diastolic blood pressure measurements within the two groups showed no substantial difference because they both remained between 61 to 100 mmHg. The respiratory rates measured in patients receiving ketamine treatment reached 18.26 ± 2.5 breaths/min while patients on propofol had rates of 17.96 ± 2.6 breaths/min. The ketamine group showed a slightly higher reading of oxygen saturation at 96.38% compared to 95.44% in the propofol group. The patients who received ketamine maintained elevated heart rates at 91.04 ± 13.4 bpm rather than patients receiving propofol who showed lower rates at 88.20 ± 14.2 bpm. The effectiveness of ketamine and propofol was similar for trauma patients undergoing RSI because both drugs produced equivalent times to LOC and equivalent pain sensations. Complete assessment of agent effectiveness for RSI should include evaluation of their respiratory and hemodynamic impact on trauma patients to determine the best clinical treatment approach.